Three dimensional metal/N-doped nanoplate carbon catalysts for oxygen reduction, the reason for using a layered nanoreactor - Yeganeh Ghotbi, M. (Nature Publishing Group, 2018)
A layered nanoreactor (zinc hydroxide gallate/nitrate nanohybrid) has been designed as a nano-vessel to confine the gallate/nitrate reaction inside zinc hydroxide layers for production of metal/nitrogen-doped carbon catalysts. Metals (Fe2+, Co2+ and Ni2+) doped and bare zinc hydroxide nitrates (ZHN) were synthesized as the Î±-phase hydroxide hosts. By an incomplete ion-exchange process, nitrate anions between the layers of the hosts were then partially replaced by the gallate anions to produce the layered nanoreactors. Under heat-Treatment, the reaction between the remaining un-exchanged nitrate anions and the organic moiety inside the basal spacing of each nanohybrid plate resulted in obtaining highly porous 3D metal/nitrogen-doped carbon nanosheets. These catalysts were then used as extremely efficient electrocatalysts for catalyzing oxygen reduction reaction (ORR). This study is intended to show the way to get maximum electrocatalytic activity of the metal/N-doped carbon catalysts toward the ORR. This exceptionally high ORR performance originates from the increased available surface, the best pore size range and the uniform distribution of the active sites in the produced catalysts, all provided by the use of new idea of the layered nanoreactor. Â© 2018 The Author(s).